Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To solve the system of equations given by:
[tex]\[ \begin{array}{l} 7x - 4y = -8 \\ y = \frac{3}{4}x - 3 \end{array} \][/tex]
we follow these steps:
1. Substitute the expression for [tex]\(y\)[/tex] from the second equation into the first equation:
The second equation gives [tex]\( y = \frac{3}{4}x - 3 \)[/tex].
Substitute [tex]\( y = \frac{3}{4}x - 3 \)[/tex] into the first equation:
[tex]\[ 7x - 4\left( \frac{3}{4}x - 3 \right) = -8 \][/tex]
2. Simplify the equation:
Distribute [tex]\( -4 \)[/tex] across the terms inside the parentheses:
[tex]\[ 7x - 4 \cdot \frac{3}{4}x + 4 \cdot 3 = -8 \][/tex]
This simplifies to:
[tex]\[ 7x - 3x + 12 = -8 \][/tex]
Combine like terms:
[tex]\[ 4x + 12 = -8 \][/tex]
3. Solve for [tex]\( x \)[/tex]:
Isolate [tex]\( x \)[/tex] by first subtracting 12 from both sides:
[tex]\[ 4x = -8 - 12 \][/tex]
[tex]\[ 4x = -20 \][/tex]
Divide both sides by 4:
[tex]\[ x = -5 \][/tex]
4. Substitute [tex]\( x \)[/tex] back into the second original equation to find [tex]\( y \)[/tex]:
Use the second equation [tex]\( y = \frac{3}{4}x - 3 \)[/tex]:
[tex]\[ y = \frac{3}{4}(-5) - 3 \][/tex]
Multiply:
[tex]\[ y = -\frac{15}{4} - 3 \][/tex]
Convert [tex]\(-3\)[/tex] to quarters:
[tex]\[ y = -\frac{15}{4} - \frac{12}{4} \][/tex]
Add the fractions:
[tex]\[ y = -\frac{27}{4} \][/tex]
Convert [tex]\(-\frac{27}{4}\)[/tex] to a decimal:
[tex]\[ y = -6.75 \][/tex]
Therefore, the solution to the system of equations is approximately:
[tex]\[ (x, y) = (-5.0, -6.75) \][/tex]
This is the point where the two equations intersect on the graph.
[tex]\[ \begin{array}{l} 7x - 4y = -8 \\ y = \frac{3}{4}x - 3 \end{array} \][/tex]
we follow these steps:
1. Substitute the expression for [tex]\(y\)[/tex] from the second equation into the first equation:
The second equation gives [tex]\( y = \frac{3}{4}x - 3 \)[/tex].
Substitute [tex]\( y = \frac{3}{4}x - 3 \)[/tex] into the first equation:
[tex]\[ 7x - 4\left( \frac{3}{4}x - 3 \right) = -8 \][/tex]
2. Simplify the equation:
Distribute [tex]\( -4 \)[/tex] across the terms inside the parentheses:
[tex]\[ 7x - 4 \cdot \frac{3}{4}x + 4 \cdot 3 = -8 \][/tex]
This simplifies to:
[tex]\[ 7x - 3x + 12 = -8 \][/tex]
Combine like terms:
[tex]\[ 4x + 12 = -8 \][/tex]
3. Solve for [tex]\( x \)[/tex]:
Isolate [tex]\( x \)[/tex] by first subtracting 12 from both sides:
[tex]\[ 4x = -8 - 12 \][/tex]
[tex]\[ 4x = -20 \][/tex]
Divide both sides by 4:
[tex]\[ x = -5 \][/tex]
4. Substitute [tex]\( x \)[/tex] back into the second original equation to find [tex]\( y \)[/tex]:
Use the second equation [tex]\( y = \frac{3}{4}x - 3 \)[/tex]:
[tex]\[ y = \frac{3}{4}(-5) - 3 \][/tex]
Multiply:
[tex]\[ y = -\frac{15}{4} - 3 \][/tex]
Convert [tex]\(-3\)[/tex] to quarters:
[tex]\[ y = -\frac{15}{4} - \frac{12}{4} \][/tex]
Add the fractions:
[tex]\[ y = -\frac{27}{4} \][/tex]
Convert [tex]\(-\frac{27}{4}\)[/tex] to a decimal:
[tex]\[ y = -6.75 \][/tex]
Therefore, the solution to the system of equations is approximately:
[tex]\[ (x, y) = (-5.0, -6.75) \][/tex]
This is the point where the two equations intersect on the graph.
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.